Apice closure in Pulp Revascularization Therapy. Case report and literature review (Research, Society and Development, 2021)
Background: Endodontic Regenerative Procedures, especially pulp revascularization therapy, have become a real option for the treatment for immature permanent teeth with open apices. This sort of approach has saved many teeth that otherwise would have been extracted. The technique is simple and effective, and can be accomplished by any odontologist. Objective: This article aimed to make a literature review to give support for a case report of an Endodontic Regenerative Procedure of a twelve-year-old male patient with immature open apice of tooth 21. Methodology: Articles were researched concerning pulp revascularization to reach root end formation. On line searches were accomplished, whose database include BVS/BIREME, Web of Science, PUBMED Central, Science Direct, Higher Level Personnel Improvement Coordinator (CAPES), The Cochrane Library, and PROSPERO). Results: the articles researched showed that Endodontic Regenerative Procedures are efficient in stimulating root end formation. The case report described matched the results offered by the articles, showing an immature open apice tooth that had its root end completely formed after pulp revascularization therapy. Conclusion: Pulp revascularization therapy is an efficient and practical treatment for immature teeth with open apices.